Trade and agroindustrialization in developing countries: trends and policy impacts - Díaz-Bonilla, Eugenio; Reca, Lucio G. (Wiley, 2000)
There have been important changes in the international trade of processed and high-value added food products from developing countries over the past several decades.... The paper highlights key trends, and explores possible reasons for the trends, focusing on trade policies in less-developed countries (LDCs) and developed countries (DCs). The paper argues that national trade policies and other economic policies appear to have been relatively supportive of agroindustrial production and exports in Asia. In contrast, policies have had more mixed effects in Latin America and the Caribbean (LAC), and seem to have been just one component in a larger array of forces inhibiting economic development in Africa." -- from Abstract.